Analisis Harga Diri Remaja Yang Memiliki Feelings Of Loneliness Terhadap Self Love - Wisda Rahmadinur (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
This study aims to determine feelings of loneliness, self-esteem has a part in the process of loving yourself (self love). This type of research is qualitative research. The focus of this study is the loneliness and self-esteem felt by adolescents at the self-love stage. In this research. The research instrument uses observation. Everyone has a different way of loving themselves. Some people who experience feelings of loneliness feel rejected by others and are unable to build deep interpersonal relationships with others. Feelings of inferiority or by others are counted as self-esteem or self-esteem. Self-esteem is a self-assessment that is determined by attitudes, interactions, gratitude, and personal acceptance of others. Self-esteem is closely related to the process of someone loving oneself. When an individual's self-esteem is high, the individual will accept himself as he is, understand that he is valuable. Someone who has high self-esteem is no longer inferior to his appearance. With a standard for oneself, a person no longer loses his confidence.